Researchers' data processing descriptions—Understanding paradata creation practices and their underpinning instrumentalities. - Huvila, Isto; Andersson, Lisa; Sköld, Olle (Journal of the Association for Information Science & Technology, 2025)
Researchers increasingly share data, both on their own initiative and as a result of requirements by funding agencies and publishers. For data to be accessible and reusable, it must be understandable. While typical metadata covers rudimentary information about data, data re‐users often need more contextual information, including paradata informative of data‐related practices and processes. To better understand the practices and types of data descriptions researchers produce, this paper analyzes 33 interviews with researchers and professionals working with archeological data in different capacities. We identified five data description practices: (1) prescribing, (2) keeping track, (3) describing (of what was done (processes); of structures, techniques, methods; of principles, rationales, decisions; of limitations of data), (4) flagging, and (5) publishing, formatting, and making available. A part evinces integrated paradata creation where paradata generation is tightly incorporated in the enactment of specific research methods, and a part standalone paradata creation prompted by aspirations to produce specific types of outputs. The findings suggest that underpinning instrumentalities, and the extent to which paradata creation is integral to research practice is central when developing means to support paradata generation, identifying where to find and how to manage it.